The Informal Waste Sector in the City of Ekurhuleni - Nyirenda, Irene N. Inan (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, landfilling has traditionally been the primary method for dealing with general municipal solid waste. However, in recent years, there has been a shift in focus towards promoting a circular economy, which has brought about a change in waste management practices. The focus is now on minimising waste generation and reducing the waste stream rather than simply disposing of it. This approach aligns with South African National Waste Management Strategy 2020, which encourages such practices. The study focused on City of Ekurhuleni and the opportunities that exist in the formalisation of the informal waste sector with particular focus on landfill waste pickers and by analysing the amount of waste disposed of at the landfill site over a six (6) year period and comparing it to the percentage of materials that informal waste pickers recovered and reclaimed, the study provided valuable insights. This study utilised a mixed-method design that involved collecting and analysing both quantitative and qualitative data through desktop surveys, face- to-face interviews, and questionnaires. The practice of informal recycling at landfill sites encounters numerous environmental and health hazards for those who reclaim materials, because the waste is not sorted before disposal. The municipality lacks adequate resources for waste reduction initiatives, regulatory framework and capacity, educational campaigns, and enforcements, unlike those carried out by private companies or organisations. The study highlighted that some of the key inconsistencies in the interpretation of informal sector activities and their integration thereof in the context of the municipal regulatory framework are vague and unsupported.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Civil and Environmental Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; ity of Ekurhuleni; Informal waste sector; recycling/reclamation; municipal solid waste; landfill waste pickers; SDG-11: Sustainable cities and communities